Studies of Peruvian Ptiliidae (Coleoptera) 3: the genus Discheramocephalus Johnson including six new species, and validation of the unavailable generic name Phytotelmatrichis Darby and Chaboo - Darby, Michael (Zootaxa, 2016)
Six new species of Discheramocephalus Johnson are described and figured: D. angustus sp. n., D. capac sp. n., D. inretitus sp. n., D. interfusus sp. n., D. malalae sp. n. and D. parvus sp. n.. The insects were collected by Dr Caroline Chaboo and her students at the University of Kansas as part of a programme to compile an inventory of leaf beetles in Peru and are the first records of the genus from the country. A key is provided. The unavailable genus Phytotelmatrichis Darby & Chaboo is made available from this publication, with Phytotelmatrichis peruviensis Darby & Chaboo 2015 as its type species.